The Sociology of the Financial Crisis: Banks, Mortgage-Backed Securities and the Modern Financial System - Egor Makarov (Journal of Economic Sociology, 2023)
This review considers the main ideas of the last Professor Fligstein’s book The Banks Did It: An Anatomy of the Financial Crisis. The book aims to analyze the financial crisis of 2008 unfolded in the mortgage securitization market in the US and its spread worldwide. The main question of the book is how the business model of mortgage securitization has been developed in the United States of America. The focus is on the structure of the banking sphere and their actions which eventually led to the financial crises. Fligstein applies a historical approach in order to analyze the business model of securitization formed in the mortgage credit market, which ultimately led to the global financial disaster. He underlines the vitality of the financial system for the economy as a whole and points out intrinsic ties between them. Within his sociological framework, the author of the book proves two major ideas. The first is that markets and the state are mutually interrelated and constitute one another. This means that the financial market is actually embedded in the sociopolitical context and shaped by the government’s actions. The second idea is that in order to understand the nature of the financial market it is crucial to analyze the business model emerged in the market. It may help forecast potential consequences of some particular economic activities and processes. The conclusion of the book is (following the title of the book) that the banks did it, although under the developing framework of mortgage securitization which roots are traced back to the crisis of the loans and savings banking model. Not only is the fundamental empirical analysis presented in the book, but also the solid economic sociology framework is successfully applied to the understanding of the financial crisis. This book is highly recommended to specialists in social sciences, as well as to the general public interested in financial crises and systems.